V make the difference Voot Resources Pvt. Ltd. - Sharma, Kush (ATLAS SkillTech University, 2025)
The global and Indian cleaning equipment industries are witnessing significant transformations driven by factors such as heightened awareness of cleanliness, rapid urbanization, technological advancements, and a strong push for sustainability. This section expands on the earlier discussion, providing a more comprehensive analysis of both the global and Indian markets, examining trends, dynamics, and key players in greater detail.
Project Report on V make the difference Voot Resources Pvt. Ltd. (2023-2025) Under the Guidance of Prof. Jaimine Vaishnav
Keywords: industries; awareness; urbanization; technological advancements